Analisis Perubahan Pemanfaatan Ruang di Kota Pekanbaru Studi Kasus :Koridor Ruas Jalan Soekarno Hatta - Yendri Rizki; Febby Asteriani (Program Studi Teknik Industri, 2020)
Pekanbaru City as the capital of Riau Province has a quite rapidly development. One of the areas that is undergoing rapid change is the Soekarno-Hatta road segment. This corridor is located in a commercial and educational area. Strategic location makes this corridor an attraction for the community and investors to invest in the region. The purpose of this study was to analyze changes in spatial use in the corridor of Soekarno Hatta Street in Pekanbaru City in 2008-2018. This researcher used a qualitative descriptive method, with spatial overlay analysis techniques in 2008 and 2018 using GIS. The results of this study are the use of space in 2008-2018 experienced a lot of changes in land use change and increased space use. In 2008 the use of space in the corridor of Soekarno Hatta Street was still largely in the form of vacant land, which has not been utilized. Most of the changes in spatial use are the emergence of new areas of land that have not been utilized. In addition, an increase in the area of ​​spatial use for economic activities amounted to 301,455m2, the area of ​​social activity change increased by 17,014m2, and the area of ​​settlement changes decreased by 10,303m2. A significant change in spatial use is in the form of increasingly widespread commercial activity in the strategic corridor area.